Social media use and political behavior of Iranian university students as mediated by political knowledge and attitude / Abdolreza Alami - Abdolreza, Alami (2017)
Social Network Sites (SNSs) are online communities where users connect to the people within their social circle or beyond it. The variety of services available in SNSs and their widespread and increasing influence as an information source and their position in the people contact has increased the number of researches on the behavior of people in the social network sites. The current research studied the relationships between the use of selected social network sites (Twitter and Facebook) and political knowledge, attitude and behavior of Iranian university students. The thesis is conducted in a mixed mode quantitative-qualitative mode of study and selected the sample of Iranian university students to collect quantitative data through a questionnaire followed by an emailed interview with lecturers and media experts. This study employed survey research design and a structured questionnaire as a means of data collection for quantitative level. The sample size in the study consisted of 382 Iranian students and 12 media experts. The findings of the current study showed that there is generally a direct and positive relation between the level of use of social networks and political knowledge, attitude and behavior. The results showed that when there is a moderate level of participation in the society, the level of political knowledge and activities are also moderate. Thus, it is probable that in the societies rather than Iran with higher levels of social participation in civil society, people have higher levels of political behavior. The findings of the study also helps the decision makers to manage the social networks in a proper and efficient way so that corrupted groups cannot downgrade the healthy stream of political participation. The current study also showed the moderation in the different sectors of the students, thus government can have a positive picture of the opposing ideas.